Paramedic-conducted Mental Health Counselling for Abused Women in Rural Bangladesh: An Evaluation from the Perspective of Participants - Naved, Ruchira T; Rimi, Nadia A; Jahan, Shamshad; Lindmark, Gunilla (Journal of Health, Population and Nutrition, 2009)
This paper reports on evaluation of an initiative to use paramedics as the first-level mental health counsellors of abused women in rural Bangladesh (2003-2004) from the perspective of the abused women who participated in one or more counselling sessions. Thirty in-depth interviews, followed by a survey (n=372), targeted to cover all participants, were conducted in 2006. Overall, the arrangement, management of ethical issues, and skills of paramedics were rated favourably. Most (89%) abused women (n=372) considered the session useful; one-fourth of these women considered it very useful; and only a few abused women considered the session useless. Usefulness of the session was expressed mostly in terms of relief attained after talking about the issue. Most (87%) women reported being encouraged to be self-confident. In a context characterized by low self-confidence of women, lack of opportunity to talk about violence, and absence of professional mental health counselling services, this initiative is sufficiently promising to warrant further testing. Key words: Battered women; Counselling; Mental health; Paramedics; Bangladesh doi: 10.3329/jhpn.v27i4.3391 J Health Popul Nutr 2009 Aug;27(4):477-491